Problems of Community Policing in Terms of Quarantine Restrictions (Law and Safety, 2021)
There have been a large number of such events in the world over the past year that cannot be called ordinary. The most difficult of them is the public challenge of spreading the COVID-19 coronavirus. Ukraine is not an exception to the countries affected by the pandemic. Measures to overcome this problem involve the coordinated work both of all government agencies and society. The police, as one of the agencies that directly enforces certain restrictions caused by anti-epidemic measures, and the contact of the population and the authorities on law enforcement activity, must master new ways of carrying out professional activities.The pandemic has complicated all public relations in the country without exception. Forms of realization of law enforcement function did not become an exception. Thus, the powers of the police have expanded to some extent due to the need to respect human rights’ restrictions in the context of combating the spread of the disease. Such functions are necessary, but their availability and necessity are questionable from the point of view of the population. The police have the duty to stop the offenses and prosecute those who violate the law regarding certain restrictions caused by the pandemic. At the same time, the majority of the population does not take seriously the appeals of health care authorities and quarantine requirements. This complicates the difficult relationship between the police and the public, since the latter does not perceive police activity in this case as legal and necessary. This leads to exacerbation of conflicts and contradictions. The constant confrontation between these entities significantly affects the level of security and quality of law enforcement activity.The relevance of the study is explained by the importance of police actions in the context of ensuring the compliance of the population with quarantine restrictions. Besides, a large amount of negative material on the Internet provokes the population to negative perception of police activities. However, it may be successful period for the formation of trust, partnership between the police and the population in regard to the situation where solving the problem (spread of the pandemic) requires the mobilization of both the population and the government.Given the above, the authors of the article have analyzed the key problems of community policing in terms of today’s challenges. The authors have developed propositions to improve the forms, methods and techniques of policing to maintain the appropriate level of public confidence in its activities.The obtained results can be further used in scientific and practical activities. The work can become a basis for further research, ground for the implementation of new forms of activities by practical units. The results of the study should be also taken into account during further rule-making activities.
Keywords: police activities in terms of quarantine; community policing; partnership; COVID-19; quarantine restrictions; public confidence